Optimization of nitrogen split application in sweet corn (Zea mays L. saccharata) - Yasasri, Landa; Majumder, Sitabhra; Shankar, Tanmoy; Paul, Sujay Kumar; Ray, Sumit (Plant Science Today, 2024)
Effective nitrogen management is essential for improving crop development and yield, especially in the cultivation of sweet corn. Conventional basal nitrogen application often leads to nitrogen loss through volatilization and denitrification. To address this issue, split nitrogen application has emerged as a promising strategy to improve nitrogen use efficiency while minimizing losses. In the summer of 2022, this experiment was carried out at the Post Graduate Research Farm of M.S. Swaminathan School of Agriculture, Paralakhemundi, Gajapati, Odisha, India to examine the effects of several nitrogen split application treatments on the growth and productivity of sweet corn. The experiment utilized a randomized complete block design (RCBD) with 10 treatments replicated thrice. Treatments included combinations of nitrogen application timings and amounts, ranging from the basal application to split applications at knee-high and tasseling stages. Results demonstrated that the treatment involving 25 % basal nitrogen, 50 % nitrogen at knee high stage and 25 % nitrogen at tasseling stage significantly maximized growth, yield and income compared to other treatments. Consequently, sweet corn cultivators in southern Odisha seeking to attain maximal development and yield should implement this nitrogen split application strategy. This study underscores the importance of tailored nitrogen management strategies in enhancing crop performance and economic returns in sweet corn cultivation.